Letter : International Brigade - Marchbank, John
035-0120-001 TELEGRAMS: "BEWARE, WALLINGFORD" TELEPHONE: WALLINGFORD 2237-2261 The National Union of Railwaymen, J. MARCHBANK, GENERAL SECRETARY J. BENSTEAD, ASSISTANT GENERAL SECRETARY TEMPORARY ADDRESS (to which all communications should be addressed) CASTLE PRIORY, WALLINGFORD, BERKS. Your Ref. HVT/AC/DT/54. In your reply refer to GS. 14/17 2nd October, 1942. Mr. H.V. Tewson, C.B.E., Assistant Secretary, Trades Union Congress, Transport House, Smith Square, LONDON, S.W.1. Dear Mr. Tewson, INTERNATIONAL BRIGADE. I am in receipt of your letter of the 30th ultimo, for which I thank you. I desire to say that I will submit same to my Executive Committee at their next Quarterly Meeting. Yours faithfully, John Marchbank 292/946/35/120